The Aroids of the Matang Massif Sarawak, Malaysian Borneo 1 : Kubah National Park - Boyce, P.C; Wong, Sin Yeng (International Aroid Society , Inc., 2007)
The Matang Massif comprises a sandstone block rising to more than 900 m (2980 ft) above sea level situated roughly 22 km (13.5 miles) NW of Kuching. Together with two isolated but geologically similar peaks – Gunung (Mount) Singgai and Gunung Berendang – the Matang Massif forms an area of outstanding biological importance not only because of the uninterrupted tropical forest encompassing a variety of ecologies but also because of the historical links to Odoardo Beccari (1843 – 1920), an Italian botanist and naturalist who can be rightly regarded as one of the founding figures of biological research in Sarawak.